Jefferson - Jackson Day Dinner invitation (1968)
The document is an invitation from the Democratic Party of California to attend the Jefferson-Jackson Day Dinner honoring Cleveland Mayor Carl Stokes. The event was held on Sunday evening, March 10, 1968, at the Century Plaza Hotel in Los Angeles, with cocktails, dinner, entertainment, and a $100 contribution requested. It lists Robert E. Wise as Dinner Chairman along with party leaders, finance committee members, and numerous county and congressional district co-chairmen involved in organizing the event.